2021
DOI: 10.3390/brainsci11060743
|View full text |Cite
|
Sign up to set email alerts
|

Parieto-Occipital Alpha and Low-Beta EEG Power Reflect Sense of Agency

Abstract: The sense of agency (SoA) is part of psychophysiological modules related to the self. Disturbed SoA is found in several clinical conditions, hence understanding the neural correlates of the SoA is useful for the diagnosis and determining the proper treatment strategies. Although there are several neuroimaging studies on SoA, it is desirable to translate the knowledge to more accessible and inexpensive EEG-based biomarkers for the sake of applicability. However, SoA has not been widely investigated using EEG. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Mind wandering indicates a decrease in the sense of agency indicating mental and autonomy, and increased alpha and beta values. In Figures 4C,D, the alpha and beta values of the parietal region are increased, and it is known as a key region for the parietal‐occipital cortex connectivity analysis 45,46 . Thus, these results show that neutral music stimulation using air conduction can activate RAS stimulation and cortical connectivity, as shown in Figure 1.…”
Section: Discussionmentioning
confidence: 60%
“…Mind wandering indicates a decrease in the sense of agency indicating mental and autonomy, and increased alpha and beta values. In Figures 4C,D, the alpha and beta values of the parietal region are increased, and it is known as a key region for the parietal‐occipital cortex connectivity analysis 45,46 . Thus, these results show that neutral music stimulation using air conduction can activate RAS stimulation and cortical connectivity, as shown in Figure 1.…”
Section: Discussionmentioning
confidence: 60%
“…Our findings for beta bands were not consistent with previous findings by de la Salle et al (2022) , potentially due to the timing of measurements at posttreatment and follow-up. In terms of cognitive functions, a recent study found that low-beta (and alpha) band powers at the parieto-occipital region reflect one’s sense of agency ( Bu-Omer et al, 2021 ), whereas a distorted sense of agency has been suggested to be linked to several neuropsychiatric disorders, including depression ( Haggard, 2017 ). Beta band activity was also previously related to anxiety ( Freeman and Quian Quiroga, 2013 ; Abhang et al, 2016 ), which itself has been used to predict suicidal ideation ( Bentley et al, 2016 ), indicating an indirect relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, awareness of a delay might be different from the delay itself, which could also be reflected in the brain. The length of the delay is associated with a sense of agency and has previously been used to raise a sense of agency (Haering and Kiesel, 2015 ; Osumi et al, 2019 ; Bu-Omer et al, 2021 ). Brain activation related to a sense of agency has been reported in several brain regions, evidenced by a power decrease in the central and bilateral parietal regions (Kang et al, 2015 ), parieto-occipital regions (Bu-Omer et al, 2021 ), and pre-supplementary motor areas (Moore et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The length of the delay is associated with a sense of agency and has previously been used to raise a sense of agency (Haering and Kiesel, 2015 ; Osumi et al, 2019 ; Bu-Omer et al, 2021 ). Brain activation related to a sense of agency has been reported in several brain regions, evidenced by a power decrease in the central and bilateral parietal regions (Kang et al, 2015 ), parieto-occipital regions (Bu-Omer et al, 2021 ), and pre-supplementary motor areas (Moore et al, 2010 ). If we consider that the sense of agency refers to a high-level representation that can be related to non-unique neurocognitive phenomena, our results might be related to a sense of agency.…”
Section: Discussionmentioning
confidence: 99%